Study of Interaction between Tigecycline and Sulbactam - Sayi̇ner, Hakan Sezgi̇n; Genç, Fatma; Kandemi̇rli̇, Fatma (Sciencedomain International, 2019)
Drug interactions can have desired, reduced or unwanted effects. The probability of interactions increases with the number of drugs taken. Side effects or therapeutic drug interactions can increase or decrease the effects of one or two drugs. Failure may result from clinically meaningful interactions. Clinicians rarely use foreseeable drug-drug interactions to produce the desired therapeutic effect. For example, when we consider two drugs each causing, peripheral neuropathy increases the likelihood of neuropathy occurrence. In this study geometry optimizations of tigecycline and sulbactam drugs and their combination have been carried out with the evaluation of B3LYP/6-311G (d, p), B3LYP/6-311G (2d, 2p) levels, and the reaction mechanism at semi empirical PM6, which was parameterized for biochemical systems and B3LYP/6-311G (d,p) levels. The main objective of the study is to understand the interaction ofsulbactam with tigecycline, to describe energetic condition of bond formation and electronic structure (orders of the broken and formed bonds). The reaction mechanisms of sulbactam with tigecycline have been studied as stepwise and concerted mechanisms using semi-empircal PM6 and B3LYP/6-311G (d,p) levels.
Keywords: 3. Good health